The time series of the heart rhythm modeling during adaptation to physical load - A. Pokhachevskiy; A. Petrov; S. Bodko; V. Seisebaev; A. Tukhfatullin; A. Gilev; A. Khomenko (National Electronic Information Consortium (NEICON), 2020)
Objective: to study the possibilities of mathematic model (M/M) of time series (TS) of the heart rhythm (HR) during the loading period (LP) to discover the best prognostic markers of the physical exercise (PE) tolerance. Materials and methods: we examined a mixed population (68 persons) of apparently healthy youth at the age from 16-23 years old (mean age - 19±3 years (M±m)). M/M TS LP was calculated using the formula: Y=aX+b, where «a» and «b» refered to the model variability parameters, «X» was the serial number and «Y» was the R-R interval size. The results of ergometric stresstest including index of power of loading, HR and M/Mduringthefirst minutes of LP were analyzed with Spearman correlation. Results: markers of M/ MTS LP can be used for studying PE tolerance. PE's power and its individual tolerance is determined by TS HR during early adaptation period (EAP). Markers of M/M EAP correlate with PE tolerance just as the average and the maximum value of heart rate defined for the entire LP. Conclusions: mathematic simulation of the time series of the HR EAP is promising for predicting the PE tolerance.